Evaluation the Effects of Complement Terminal Component (C5b-9) on Immunothrombosis in Severe and Critical COVID-19 Infections Compared to Mild Cases - Muhammed, Abdul Q. W.; Hassan, Hadi R. (Scientific Journal of Medical Research, 2022)
Background: The study aimed to evaluate the association between the complement terminal component (C5b-9) and immuno-thrombosis in severe and critical COVID-19 patients compared to mild cases. Materials and Methods: A cross-sectional study was conducted. From October 1, 2021, to May 30, 2022, 82 COVID-19 patients were recruited at Imam AL-Hussein Medical City in Kerbala, consisting of 44 males and 38 females, and their ages ranged from 25 to 85 years old. All patients tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and were hospitalized. Twenty-seven of those were diagnosed with mild COVID-19 and 27 with severe diseases, while 28 patients had critical diseases. Results: C5b-9 level significantly elevated with the severity of COVID-19. Conclusion: There is a significant correlation between complement terminal component (C5b-9) elevation and COVID-19 severity.